2006
DOI: 10.1002/chem.200600169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stereochemical Assignment of DNA Spore Photoproduct Analogues

Abstract: Investigation of the DNA repair process performed by the spore photoproduct (SP) lyase repair enzyme is strongly hampered by the lack of defined substrates needed for detailed enzymatic studies. The problem is particularly severe because the repair enzyme belongs to the class of strongly oxygen-sensitive radical (S)-adenosylmethionine (SAM) enzymes, which are notoriously difficult to handle. We report the synthesis of the spore photoproduct analogues 1 a and 1 b, which have open backbones and are diastereoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…For experimental phasing, two approaches were used: crystals of the native protein were soaked for 5 min in the cryoprotectant solution supplemented by 100 mM of 5-amino-2,4,6-triiodoisophthalic acid solution (Jena Bioscience, Jena, Germany) (16) and selenomethionine-substituted protein was crystallized and cryoprotected as described for the native protein. The substrate-bound SP lyase crystal structure was obtained by soaking crystals for 10 min in a solution containing 20 mM dinucleoside spore photoproduct (5 R –SP side synthesized as described previously (17) and shown in Supplementary Figure S1), the mother liquor, 3 mM dithiothreithol, 50 mM NaCl, 15 mM pyrophosphate, 14 mM hexametaphosphate (Sigma-Aldrich) and 15% (vol/vol) ethylene glycol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For experimental phasing, two approaches were used: crystals of the native protein were soaked for 5 min in the cryoprotectant solution supplemented by 100 mM of 5-amino-2,4,6-triiodoisophthalic acid solution (Jena Bioscience, Jena, Germany) (16) and selenomethionine-substituted protein was crystallized and cryoprotected as described for the native protein. The substrate-bound SP lyase crystal structure was obtained by soaking crystals for 10 min in a solution containing 20 mM dinucleoside spore photoproduct (5 R –SP side synthesized as described previously (17) and shown in Supplementary Figure S1), the mother liquor, 3 mM dithiothreithol, 50 mM NaCl, 15 mM pyrophosphate, 14 mM hexametaphosphate (Sigma-Aldrich) and 15% (vol/vol) ethylene glycol.…”
Section: Methodsmentioning
confidence: 99%
“…The wild-type, reconstituted SP lyase (125 μM) was incubated with 5 mM dithiothreitol, 2 mM SAM, 250 μM SP side (5 R –SP side or 5 S –SP side synthesized as described previously (17) and shown in Supplementary Figure S1) in a Tris buffer (50 mM Tris–HCl pH 8 and 500 mM NaCl) and the repair reaction was started by adding 3 mM sodium dithionite. Control reactions were performed by omitting sodium dithionite.…”
Section: Methodsmentioning
confidence: 99%
“…Some earlier studies suggested that SPL recognizes and repairs the 5S-isomer (65,66), which has been corrected (67). In a recent SPL structure solved by Benjdia et al (68), the enzyme contains a dinucleoside 5R-SP, further confirming that the 5R-isomer is the SPL substrate.…”
Section: Spl Repairs the 5r-isomer Of Spmentioning
confidence: 58%
“…48,63,67 Besides using the traditional photochemical approach to generate the SP, synthetic chemistry have been developed to prepare the dinucleotide and dinucleoside SP as well as incorporate SP into the oligomer strand. 44,64,6668,106 Although the syntheses are lengthy and the overall yields are low, SP preparation in milligram scale has become a realistic expectation. The progress in the SP synthesis resulted in the first structural characterizations of SP.…”
Section: Discussionmentioning
confidence: 99%